2020
DOI: 10.5713/ajas.19.0290
|View full text |Cite
|
Sign up to set email alerts
|

MiR-126-3p inhibits apoptosis and promotes proliferation by targeting phosphatidylinositol 3-kinase regulatory subunit 2 in porcine ovarian granulosa cells

Abstract: Objective: Numerous studies have indicated that the apoptosis and proliferation of granulosa cells (GCs) are closely related to the normal growth and development of follicles and ovaries. Previous evidence has suggested that miR-126-3p might get involved in the apoptosis and proliferation of GCs, and phosphatidylinositol 3-kinase regulatory subunit 2 (<i>PIK3R2</i>) gene has been predicted as one target of miR-126-3p. However, the molecular regulation of miR-126-3p on <i>PIK3R2</i> and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In addition, we further demonstrated that miR-126-3p down-regulate PIK3R2 expression through post-transcriptional regulation by binding to the sequence in the 3' untranslated region of PIK3R2. Interestingly, in line with our study, another study by Xiaofeng Zhou showed that miR-126-3p were able to inhibit apoptosis by targeting PIK3R2 in porcine OGCs, which supports the results of this study [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we further demonstrated that miR-126-3p down-regulate PIK3R2 expression through post-transcriptional regulation by binding to the sequence in the 3' untranslated region of PIK3R2. Interestingly, in line with our study, another study by Xiaofeng Zhou showed that miR-126-3p were able to inhibit apoptosis by targeting PIK3R2 in porcine OGCs, which supports the results of this study [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Like miR-222-3p, miR-126-5p is also associated with PCOS [ 22 , 23 ]. Studies in rats and pigs have shown that miR-126-5p in ovarian granulosa cells promotes vascular growth and inhibits apoptosis [ 24 , 25 , 26 ]. There is limited research on the role of miR-2954 in reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-126 negatively regulated PIK3R2 protein expression in immature porcine Sertoli cells. It has been widely reported that miR-126 targets the PIK3R2 gene and represses its expression through a conserved binding site in a diverse group of animal species [ 13 , 33 , 34 ]. Previous studies have demonstrated that the PIK3R2 gene, a member of the PI3K family, encodes p85β, an enzyme involved in the production of 3-polyphosphoinositides [ 35 ].…”
Section: Discussionmentioning
confidence: 99%